Oath of loyalty [compact disc, unabridged] - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2022)
With President Anthony Cook convinced that Mitch Rapp poses a mortal threat to him, Rapp agrees to leave the country and stay in plain sight for as long as Cook controls the White House. When Cook's power-hungry security adviser leaks the true identity of his partner, Claudia Gould, Rapp races to neutralize the enemies organizing against her and discovers that a new generation of assassins is on her trail. A killer known to intelligence agencies only as Legion.